SOSIALISASI PENGGUNAAN ANTIBIOTIK YANG TEPAT DAN DAGUSIBU DI DESA MULAWARMAN KECAMATAN TENGGARONG SEBERANG KABUPATEN KUTAI KARTANEGARA - Henny Nurhasnawati; Anadafti Veta Anadafti Veta; Deila Putri Maharani; Herlan Hidayat Putra; Mirna Anjelika Imas; Muhamad Alif Ramadhan Pratama; Rolita; Stefania Maria Mercindy Stefania Maria Mercindy (Jurnal Abdi Masyarakat Kita, 2026)
Abstract: Antibiotic resistance is a global health threat exacerbated by the low level of public knowledge about the proper use of drugs. This community service activity aims to increase the understanding and knowledge of residents of Mulawarman Village, Tenggarong Seberang District, Kutai Kartanegara regarding the wise use of antibiotics and proper drug management through the socialization of the DAGUSIBU (Get, Use, Save, Dispose) program. The method used was counseling and socialization using PowerPoint media and brochures which was carried out on August 14, 2025, with evaluation of participant understanding using pre-tests and post-tests. The evaluation results showed a significant increase in knowledge, where the average level of participant understanding increased from 45.45% in the pre-test to 54.55% in the post-test. This proves that direct socialization and education are effective in increasing public health literacy as a preventive effort to suppress the rate of antibiotic resistance at the community level.